2016
DOI: 10.1126/science.aad8786
|View full text |Cite
|
Sign up to set email alerts
|

A beak size locus in Darwin’s finches facilitated character displacement during a drought

Abstract: Ecological character displacement is a process of morphological divergence that reduces competition for limited resources. We used genomic analysis to investigate the genetic basis of a documented character displacement event in Darwin's finches on Daphne Major in the Galápagos Islands: The medium ground finch diverged from its competitor, the large ground finch, during a severe drought. We discovered a genomic region containing the HMGA2 gene that varies systematically among Darwin's finch species with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
239
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 230 publications
(258 citation statements)
references
References 43 publications
13
239
2
1
Order By: Relevance
“…In the present study, the large differences in the principal toxin expression between NK-M and NK-T were most likely the result of directional selection, potentially due to local selective pressures and/or coevolution with distinct prey populations or species. Adaptive expression variations have been well documented in animals including venomous snakes, where the expression variability has been shown to account for the differences in venom function, particularly intraspecific venom function (Lamichhaney et al, 2015, 2016; Margres et al, 2016; Zhang & Reed, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the large differences in the principal toxin expression between NK-M and NK-T were most likely the result of directional selection, potentially due to local selective pressures and/or coevolution with distinct prey populations or species. Adaptive expression variations have been well documented in animals including venomous snakes, where the expression variability has been shown to account for the differences in venom function, particularly intraspecific venom function (Lamichhaney et al, 2015, 2016; Margres et al, 2016; Zhang & Reed, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Both pygmy mice and dwarf rabbits show altered craniofacial development, characterized by shortened heads (Zhou et al 1995) (Figure 1). Interestingly, a recent study showed that HMGA2 is a major locus affecting craniofacial development (beak size) in Darwin's finches (Lamichhaney et al 2016), but in that case the phenotypic effect is likely caused by regulatory changes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably two variants of a gene (HMGA2) with major effects on beak size changed in frequency in the expected direction as a result of natural selection in 2004-2005 [56]. Less predictable are the effects of environmental extremes on evolution [57].…”
Section: Demography Of Birdsmentioning
confidence: 99%